Ancient mining from southwest Bulgaria (based on data from Archaeological information system “Archaeological Map of Bulgaria”) - Ivo Cholakov (Българско е-Списание за Археология, 2025)
The subject of this paper is a review of the archaeological sites associated with ancient ore mining and metallurgy, located in Southwest Bulgaria. The information for this type of sites is drawn mainly from the data recorded in the Archaeological information system “Archaeological Map of Bulgaria” (AIS AKB), as well as from academic publications on the topic. The region under study includes archaeological sites located on the territory of three administrative districts in Bulgaria – Pernik, Kyustendil and Blagoevgrad. The vast majority of sites associated with ore mining are found in the Kraishte region, situated in today’s Pernik and Kyustendil districts and partly in Republic of Serbia and Republic of North Macedonia. The presence of gold, lead, copper, silver and iron deposits was appreciated already in ancient times, and their exploitation became a major livelihood for the local population. Most numerous are the sites dated to Antiquity, followed by sites from the Middle Ages, but the extraction of precious metals along some rivers may be dated to the Bronze Age as well. There are only a few sites where traces of both mining and metallurgical production are found. The places where slag is registered comprise mainly settlements and the materials discovered are rather from the manufacture of metal items than metal extraction.